Amsacrine Derivatives Selectively Inhibit Mycobacterial Topoisomerase I (TopA), Impair M. smegmatis Growth and Disturb Chromosome Replication - Szafran, Marcin J.; Kołodziej, Marta; Skut, Patrycja; Medapi, Brahmam; Domagała, Agnieszka; Trojanowski, Damian; Zakrzewska-Czerwińska, Jolanta; Sriram, Dharmarajan; Jakimowicz, Dagmara (Frontiers in Microbiology, 2018)
Amsacrine, which inhibits eukaryotic type II topoisomerase via DNA intercalation and stabilization of the cleavable topoisomerase-DNA complex, promotes DNA damage and eventually cell death. Amsacrine has also been shown to inhibit structurally distinct bacterial type I topoisomerases (TopAs), including mycobacterial TopA, the only and essential topoisomerase I in Mycobacterium tuberculosis. Here, we describe the modifications of an amsacrine sulfonamide moiety that presumably interacts with mycobacterial TopA, which notably increased the enzyme inhibition and drug selectivity in vivo. To analyse the effects of amsacrine and its derivatives treatment on cell cycle, we used time-lapse fluorescence microscopy (TLMM) and fusion of the β-subunit of DNA polymerase III with enhanced green fluorescence protein (DnaN-EGFP). We determined that treatment with amsacrine and its derivatives increased the number of DnaN-EGFP complexes and/or prolonged the time of chromosome replication and cell cycle notably. The analysis of TopA depletion strain confirmed that lowering TopA level results in similar disturbances of chromosome replication. In summary, since TopA is crucial for mycobacterial cell viability, the compounds targeting the enzyme disturbed the cell cycle and thus may constitute a new class of anti-tuberculosis drugs.